The Inauguration of Faisal Bin Al -husain as Iraq King (A Study of British Documents) - عبدالله حميد العتابي (College of Education for Women, 2019)
Husain as a king of Iraq. This paper deals with the British communication with faisel . then Winston Churchill's speech in British common house .then fodlowed by arriving faisal to Iraq after that the referend um faisel . The his claims of British maneuver lastly coronation on faisal & his inauguration as a king of Iraq.